(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the military-strategic significance of the Kogon–Termez railway constructed by the Russian Empire in the late 19th and early 20th centuries. The railway served not only as a means of economic and transport development but also as a tool for strengthening Russia’s military control over Turkestan. Special attention is given to the railway’s proximity to the Afghan border, its role within the geopolitical rivalry known as the «Great Game» and its strategic importance in the Russian Empire’s expansion toward South Asia.